2005
DOI: 10.1103/physreva.71.043804
|View full text |Cite
|
Sign up to set email alerts
|

Induced transparency and absorption in coupled whispering-gallery microresonators

Abstract: Optical behavior analogous to electromagnetically induced transparency and absorption is observed in experiments using coupled fused-silica microspheres. This behavior results from interference between coresonant whispering-gallery modes of the two spheres. Coupled-resonator-induced transparency and absorption are observed. Which effect is seen depends on the strength of coupling of incident light from a tapered fiber into the first sphere and on the strength of coupling between the two spheres. The observed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
118
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(123 citation statements)
references
References 23 publications
3
118
1
1
Order By: Relevance
“…In 2004, Smith et al theoretically studied the EIT resonance in a multiple directly coupled cavity system [31], as shown in Figure 5A. Then in 2005, Naweed et al observed EIT resonance in two directly coupled silica microspheres [34], as shown in Figure 5B. In 2007, Totsuka et al experimentally studied the slow light effect when EIT resonance appears in two directly coupled microsphere system ( Figure 5C) [36].…”
Section: All-optical Eit In Coupled Microcavitiesmentioning
confidence: 99%
“…In 2004, Smith et al theoretically studied the EIT resonance in a multiple directly coupled cavity system [31], as shown in Figure 5A. Then in 2005, Naweed et al observed EIT resonance in two directly coupled silica microspheres [34], as shown in Figure 5B. In 2007, Totsuka et al experimentally studied the slow light effect when EIT resonance appears in two directly coupled microsphere system ( Figure 5C) [36].…”
Section: All-optical Eit In Coupled Microcavitiesmentioning
confidence: 99%
“…Fano resonances and EIT have been observed in a silica microsphere 28 , a polydimethyl-siloxane-coated silica microtoroid with two WGMs 29 , two directly coupled silica microspheres 25,30 , two indirectly coupled silicon microrings 26 , and indirectly coupled microdisk and microtoroid 31 . In these EIT implementations, two frequency-degenerate WGMs of high-and low-quality factors (Q) are coupled, and destructive interference of the optical pathways cancels the absorption leading to a narrow transmission peak.…”
mentioning
confidence: 98%
“…If a frequency detuning is introduced, the transmission spectra show sharp asymmetric Fano resonances. ATS has been observed in directly coupled silica microspheres 25 , directly coupled silica microtoroids 34 , hybrid systems formed by directly coupling polydimethyl-siloxane-coated silica microtoroids with silica microtoroids or microspheres 35 and directly coupled polyethylene and quartz disks in the THz domain 36 . In these systems, ATS originates from the lifting of the frequency degeneracy of the eigenmodes, hence their splitting into two resonances because of strong inter-resonator coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since EIT results from destructive quantum interference, it has been recognized that similar coherence and interference effects can also occur in classical systems, such as plasma [7,8], coupled optical resonators [9,10,11,12,13], mechanical or electric oscillators [14].…”
mentioning
confidence: 99%